2017
DOI: 10.1007/s10096-017-3043-3
|View full text |Cite
|
Sign up to set email alerts
|

Suggested new breakpoints of anti-MERS-CoV antibody ELISA titers: performance analysis of serologic tests

Abstract: To provide optimal cut-off values of anti-Middle East respiratory syndrome coronavirus (MERS-CoV) serologic tests, we evaluated performance of ELISA IgG, ELISA IgA, IFA IgM, and IFA IgG using 138 serum samples of 49 MERS-CoV-infected patients and 219 serum samples of 219 rRT-PCR-negative MERS-CoV-exposed healthcare personnel and patients. The performance analysis was conducted for two different purposes: (1) prediction of neutralization activity in MERS-CoV-infected patients, and (2) epidemiologic surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Recent work examining a panel of MERS‐CoV patient serum has suggested that S ELISA sensitivity can be increased by lowering the breakpoint in MERS‐CoV S ELISAs . While doing this would capture a larger percentage of patients who seroconvert, we have seen several patients who never develop detectable MERS‐CoV S antibodies, but do develop N antibodies (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work examining a panel of MERS‐CoV patient serum has suggested that S ELISA sensitivity can be increased by lowering the breakpoint in MERS‐CoV S ELISAs . While doing this would capture a larger percentage of patients who seroconvert, we have seen several patients who never develop detectable MERS‐CoV S antibodies, but do develop N antibodies (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The present study used EUROIMMUN ELISA based on the purified spike protein domain S1 antigen for determining the seropositivity rate in camels and humans. The performance of this kit for testing MERS-CoV infection has been previously evaluated and it was stated that using a confirmatory test after initial screening of samples with this ELISA is not mandatory [33]. It has been also successfully used by other authors with 99% specificity compared to microneutalization test [11].…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantitative anti-MERS-CoV IgG camel and human ELISAs (Euroimmun, Lübeck, Germany) were used in the present study to detect specific IgG antibodies against MERS-CoV in camel and human sera, respectively. The kits utilize the purified spike protein domain S1 antigen of MERS coronavirus (MERS-CoV S1) based on its high sensitivity and high specificity [11,13,33]. Briefly, the serum samples were diluted (1:101) and the test procedure was then performed as per the manufacturer's instructions.…”
Section: Serological Assaymentioning
confidence: 99%
“…However, these assays are timeconsuming, laborious, and require high-level biosafety facilities [53,60]. The performance of the commercial MERS-CoV S1-based ELISA has been assessed by different groups [18,35,51,65,66], all of which have shown that the sensitivity of this assay needs to be improved, as it shows high cut-off values from the optical density (OD) ratio (the manufacturer's instructions provided a higher breakpoint for ELISA IgG to warrant specificity, with a borderline OD ratio cut-off of 0.8-1.1 and positive ≥1.1). LISA is characterized by rapid preparation, ultra-sensitivity, high-throughput, and simple operation [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods can be used to detect serum antibodies against MERS-CoV, such as enzyme-linked immunosorbent assay (ELISA), microneutralization (MN), immunofluorescence assay (IFA), the plaque reduction neutralization test (PRNT), and the pseudovirus particle neutralization test (ppNT). Among these assays, MN, IFA, and PRNT depend on virus cultivation, and thus, require equipment and facilities located within a Biosafety Level 3 (BSL-3) laboratory [1,3,12,18,35,39,[50][51][52][53][54]. While there are commercial anti-MERS-CoV serologic test kits for humans and animals including ELISA and IFA, rapid and sensitive serological assays for the detection of anti-MERS-CoV IgG independent of purified protein, specific secondary antibody, virus cultivation and BSL-3 facilities are still urgently needed.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%